Моделювання ризику ураження пожежами лісових екогеосистем у Харківському регіоні - Буц, Юрій Васильович (НТУ "ХПІ", 2017)
Метою дослідження стало встановлення ймовірності виникнення пожеж та ризику ураження лісових екогеосистем у Харківському регіоні. Проведені розрахунки ймовірності виникнення пожеж в екогеосистемах. Питомий ризик пошкодження використаний як ефективний показник для картографування й порівняльної оцінки ризику від небезпечних природних і техноприродних процесів, які призводять до тран- сформації екогеосистем. За даними проведених розрахунків створено картографічний матеріал, що характеризує ризик ураження території внаслідок лісових пожеж.

The actual problem of the present is the establishment of the probability of occurrence of fires and the risk of their spread (defeat) in ecogeosystems. From the point of view of ecological safety and rational nature management, it is important to determine the consequences of the influence of forest fires on the ecogeosystem, which in this case is expressed by the risk of spreading or the area passed by fire. The aim of the study was to establish the likelihood of fires and the risk of destruction of forest ecogeosystems in the Kharkov region. According to statistical data of the Kharkov regional department of forestry and hunting economy, the probability of occurrence of fires in ecogeosystems of forest massifs is calculated. The specific risk of damage is used as an effective indicator for mapping and comparative assessment of the risk of hazardous natural and techno-natural processes that lead to the transformation of ecogeosystems, especially in the absence of reliable information on the location and cost of individual ecogeosystems. According to the calculations carried out, cartographic material is created that characterizes the risk of damage to the territory as a result of forest fires. For the cartographic basis, the map of the administrative-territorial structure of the Kharkov region, with the predetermined boundaries of the forestry enterprises of the Kharkov regional department of forestry and hunting, was chosen. The differentiation of the background displays the probability of the destruction of the territory of forest tracts as a result of fires on the map. An analysis of the created cartographic material showed that out of the 10 presented state forestry enterprises, 6 are within an acceptable risk level for the probability of the territory's destruction by forest fires. Three forests in the Kharkiv region are estimated to be at risk, requiring detailed justification. Ecological systems of the Izyum farm are characterized by a risk that is acceptable only in special circumstances. It should be noted that the 2008 forest fire with a total area of more than 1600 hectares significantly influenced the increased risk of lands of this forestry
A design of risk of defeat the fires of forest ecogeosystems is in the Kharkov region
Keywords: пожежна небезпека; визначення ризику; картографування; пірогенна трансформація; fire hazard; risk identification; mapping; pyrogenic transformation